2018
DOI: 10.1086/699652
|View full text |Cite
|
Sign up to set email alerts
|

World Citizens on the Periphery: Threat and Identification with Global Society

Abstract: Who identifies as a world citizen? Many scholars argue that transnational connections are the primary conduits for global cultural diffusion and, therefore, that affluent residents of the densely connected global core should be the most likely to identify with global society. However, empirical studies have shown that global identification is common on the global periphery. We build on theories suggesting that individuals may emphasize expansive identities when particularistic identities fail to provide a sens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 131 publications
1
13
0
Order By: Relevance
“…The handful of studies comparing cooperative internationalism between residents of core and peripheral countries are inconclusive but are more consistent with the idea that people form their interpretations of globalization based on local considerations. Most of these studies have found no difference in cooperativeinternationalist attitudes and global identification on the basis of country-level factors that include per capita gross domestic product (GDP) and various measures of economic, political, and social globalization (Zhou 2016), with a handful indicating that such attitudes may be more common on the global periphery (Gorman and Seguin 2018;Hurwitz et al 1993;Pichler 2011). Even fewer studies have systematically compared proglobal orientations between elites and non-elites in core and peripheral contexts, although Gorman and Seguin (2018) find that repressed minorities are often more likely to identify as world citizens.…”
Section: Local Uses and Interpretations Of Globalizationmentioning
confidence: 99%
See 4 more Smart Citations
“…The handful of studies comparing cooperative internationalism between residents of core and peripheral countries are inconclusive but are more consistent with the idea that people form their interpretations of globalization based on local considerations. Most of these studies have found no difference in cooperativeinternationalist attitudes and global identification on the basis of country-level factors that include per capita gross domestic product (GDP) and various measures of economic, political, and social globalization (Zhou 2016), with a handful indicating that such attitudes may be more common on the global periphery (Gorman and Seguin 2018;Hurwitz et al 1993;Pichler 2011). Even fewer studies have systematically compared proglobal orientations between elites and non-elites in core and peripheral contexts, although Gorman and Seguin (2018) find that repressed minorities are often more likely to identify as world citizens.…”
Section: Local Uses and Interpretations Of Globalizationmentioning
confidence: 99%
“…Most of these studies have found no difference in cooperativeinternationalist attitudes and global identification on the basis of country-level factors that include per capita gross domestic product (GDP) and various measures of economic, political, and social globalization (Zhou 2016), with a handful indicating that such attitudes may be more common on the global periphery (Gorman and Seguin 2018;Hurwitz et al 1993;Pichler 2011). Even fewer studies have systematically compared proglobal orientations between elites and non-elites in core and peripheral contexts, although Gorman and Seguin (2018) find that repressed minorities are often more likely to identify as world citizens. Taken together, scholarship in this area suggests that people on the global periphery may use global connections to further their local goals, and may, therefore, be more supportive of international cooperation than once thought.…”
Section: Local Uses and Interpretations Of Globalizationmentioning
confidence: 99%
See 3 more Smart Citations